1997
DOI: 10.1136/ard.56.8.470
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and sources of native and prosthetic joint infection: a community based prospective survey

Abstract: Objectives-To determine the incidence and sources of bacterial arthritis in the Amsterdam health district and the maximum percentage of cases that theoretically would be preventable. Methods-Patients with bacterial arthritis diagnosed between 1 October 1990 and 1 October 1993 were prospectively reported to the study centre by all 12 hospitals serving the district. Data were gathered on previous health status, source of infection, and microorganisms involved. Results-188 episodes of bacterial arthritis were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
212
4
23

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(257 citation statements)
references
References 33 publications
(8 reference statements)
18
212
4
23
Order By: Relevance
“…Our data suggested no clear evidence between postoperative UTI and joint infection, which is consistent with the literature [22,24,36,41]. The majority of bacteria we observed were not enteric pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…Our data suggested no clear evidence between postoperative UTI and joint infection, which is consistent with the literature [22,24,36,41]. The majority of bacteria we observed were not enteric pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…Septic arthritis is a common clinical problem [1][2][3] and previous studies have identified the importance of early diagnosis and treatment to reduce the risk of chondral damage and poor long-term function due to complications of early arthrosis. Vispo Seara et al [18] found that early surgical intervention (mean 12 days) in large joint septic arthritis led to improved functional outcomes and fewer repeat surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this condition is reported to be up to 7.8 per 100,000 per year [1][2][3]. The progression can be very rapid with potentially lifethreatening complications.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[6][7][8][9][10][11][12][13][14] Once an infection is diagnosed, a number of therapeutic approaches may be adopted. The selection of a particular approach depends on host factors (age, baseline mobility, comorbidities, etc.…”
Section: Risk Factorsmentioning
confidence: 99%